Pathologic response and safety of preoperative treatment regimens in gastric cancer undergoing D2 gastrectomy: a real-world cohort study - Liu, Penghui; Li, Na; Guo, Jiwu; Wang, Jizhen; Wang, Zhen; Zhao, Gengyutong; Mou, Ziyuan; Mao, Jie (Frontiers in Immunology, 2026)
ObjectiveTo compare pathological response and safety among three preoperative treatment regimens—chemotherapy alone, chemotherapy plus immunotherapy, and chemotherapy plus immunotherapy and targeted therapy—in gastric cancer undergoing D2 gastrectomy, and to assess biomarker associations with response.MethodsWe retrospectively included 195 patients who received preoperative systemic therapy followed by D2 gastrectomy: chemotherapy alone (n = 47), chemotherapy plus immunotherapy (n = 100), or chemotherapy plus immunotherapy and targeted therapy (n = 48). Preoperative therapy was considered neoadjuvant for cM0 disease and conversion therapy for selected baseline cM1 disease. The primary endpoint was MPR (including pCR). pCR was also reported separately as a subset of MPR; secondary endpoints were preoperative treatment-related adverse events, surgical and pathological outcomes, and disease-free and overall survival (DFS, OS). Logistic regression was used to identify factors associated with MPR; DFS and OS were evaluated with Kaplan–Meier and Cox models.ResultsOverall pCR and MPR rates were 20.5% and 40.0%. MPR rates were 27.7%, 37.0%, and 58.3% in the chemotherapy, chemotherapy+immunotherapy, and triple-regimen groups. The triple regimen improved MPR versus chemotherapy in unadjusted analysis, but regimen type was not an independent predictor after adjustment. Lauren intestinal subtype and PD-L1 CPS ≥5 were strongly associated with higher MPR, and in PD-L1–low tumors the triple regimen was associated with higher MPR. Rates of grade ≥3 adverse events and postoperative complications were similar across groups. DFS and OS did not differ significantly; higher cN stage and older age were associated with worse outcomes.ConclusionPreoperative treatment regimens containing immunotherapy, particularly the triple combination, improved pathological response without increasing preoperative risk. Tumor biology—especially Lauren subtype and PD-L1 expression—had a greater impact on response than regimen intensity, supporting biomarker-guided strategies.